The VITA Project: Phenotypic Resistance to Activated Protein C and FV Leiden Mutation in the General Population - Tosetto, Alberto; Rodeghiero, Francesco; Missiaglia, Edoardo; Gatto, Elisabetta (Thrombosis and Haemostasis, 1997)
Resistance to activated protein C (APC) has been recently identified as a common abnormality of the clotting system that significantly increases the risk of venous thromboembolism. The distribution of plasma response to APC in the general population and the variables potentially influencing it are however unknown. In this study, we analyzed the data from the first 4,000 subjects enrolled in the Vicenza Thrombophilia and Atherosclerosis (VITA) Project to identify the demographic and laboratory variables affecting the plasma response to APC. Plasma response to APC, expressed as APC-ratio, was significantly influenced not only by the presence of the FV Leiden mutation but also by the aPTT ratio, triglycerides, fibrinogen and cholesterol level and by pill use, ABO blood group, gender, smoke, body-mass index and age. The effect of these variables was independent of the presence of the FV Leiden mutation, and adjustment for their effect improved the discriminating efficiency of the APC-ratio for the presence of the FV Leiden mutation. Notwithstanding adjustment, the APC ratio was unsuitable for screening purposes in the general population (positive predictive value 82.7%).